High performance fiber-shaped supercapacitors based on core–shell fiber electrodes with adjustable surface wrinkles and robust interfaces. Issue 31 (28th July 2021) - Shi, Hang; Chen, Song; Shi, Wei; Peng, Zefei; Li, Junyun; Liu, Zelin; Zhang, Guangyong; Liu, Lan
Abstract : Constructing micro PPy wrinkles on the rGO/Alg fiber surface with strong interactions at the interface endows the fiber with excellent specific capacitance and cycling stability. Abstract : Fiber-shaped supercapacitors (FSSCs) have the advantages of light weight, small size and good compatibility with the textile industry. However, it is the small size that restricts both the mass-loading and loading stability of active materials on fiber electrodes, which further influences the electrochemical and mechanical performance of the devices. In this work, to increase the surface area and interfacial stability, we designed an adjustable wrinkled polypyrrole (PPy) sheath on the surface of a reduced graphene oxide/alginate (rGO/Alg) hydrogel fiber core via in situ polymerization. Because of the large surface area of the PPy wrinkles, the obtained core–shell fiber showed a high volumetric specific capacitance of 326.20 F cm −3 in liquid electrolyte. Besides, with the robust interfacial interaction between the PPy and the flexible rGO/Alg matrix, the fiber displayed an excellent cycling stability with 91.61% capacitance retention after 10 000 charge/discharge cycles at a high current density of 10 A cm −3 . And the assembled symmetrical supercapacitor also showed 83.45% capacitance retention after 2000 bending cycles up to 180° and delivered an energy density of 2.15 mW h cm −3 at a high power density of 493.6 mW cm −3, further demonstrating its high stability and flexibility. This work provides a new strategy for the design of stable micro-wrinkles on the fiber surface for high performance FSSCs.